A Application Approach to Playing to Increase Learning Results and Self-Trust Straddle the Vault - Ramadhan, Aditya Rizky (JOURNAL RESPECS (Research Physical Education and Sports), 2023)
This study aims to determine whether there is an increase in the learning process by using a playful approach to learning outcomes and confidence to jump on the students for grade XI Chemical Engineering in SMK Negeri 7 Bandung. The method used in this research is the Classroom Action Research method to solve the existing problems. The population of this study is the students of boys and girls in SMK Negeri 7 Bandung grade XI Industrial Chemical Engineering; during the sample in this study, as many as 35 people. Instruments used in this study showed the results of learning using skill tests, observation, and field notes, while the instrument confidence using questionnaires; based on the results of research data obtained, it can be known that learning outcomes occur increased and exceeded the KKM 80%. In contrast, confidence is also happening with the improvement of "strong" interpretation exceeding 80%. So, the approach to play can increase self-confidence and learning results by straddling the vault. Limitation and recommendation: sport education determine to improve the learning process by using a playful approach.